The outcome of PDA ligation by mini-thoracotomy in premature neonates: A single hospital experience - Saeed Al Hindi; Noor Alhashimi; Husain Al Aradi; Zainab Irshad (EL-Med-Pub, 2020)
Background: Various thoracotomy practices have been employed for occlusion of patent ductus arteriosus (PDA) which are not amenable to medical management. We report our preliminary experience of using a mini-thoracotomy approach in small premature infants and determining survival outcomes in relation to factors such as gender, birth weight, age, and type of ventilation used intraoperatively.  Methods: Between January 2004 and December 2012, 52 consecutive premature infants with an echocardiographic diagnosis of isolated PDA, which are not amenable to medical treatment, were included. Those with chromosomal abnormalities, major cardiac congenital anomalies aside from septal defects, and infants who did not receive mechanical ventilation in the first week of life were excluded. The median gestational age was 28 weeks and the median gestational weight at surgery was 705g. The median PDA size was 3.8mm, ranging from 1.6 to 5mm. Twenty-nine patients were given non-selective ventilation and twenty-three were anesthetized using selective right-lung ventilation using a 2-F balloon catheter for arterial embolectomy. A left lateral mini-thoracotomy was performed in all infants and PDA closure achieved by double ligation using zero silk sutures. Results: The median operative time and mean length of hospital stay were 45 minutes and 90 days, respectively. No major hemorrhage requiring blood transfusion occurred during the surgery. The survival rate until hospital discharge was 88.5%. There were no mortalities associated with the surgery itself. Six (11.5%) neonates died postoperatively because of prematurity (p-value=1.000). Pneumonia and atelectasis were among the few complications encountered post ligation. An interesting association was recognized between ventilation and surgical complications; that is neonates who underwent selective right ventilation did not experience any of the complications mentioned above in comparison to those who were put under non-selective ventilation (p-value <0.001). Conclusion: Closure of PDA by double ligation via a left mini-thoracotomy in small premature infants proved to be safe and effective in providing pediatric surgeons adequate exposure within confined and delicate anatomic spaces. No mortalities or major complications were encountered.